Antibiotic resistance, genome analysis and further safe traits of Clostridium perfringens ICVB082; a strain capable of producing an inhibitory compound directed only against a closely related pathogenic strain. (April 2020) - Vieco-Saiz, Nuria; Belguesmia, Yanath; Vachée, Anne; Le Maréchal, Caroline; Salvat, Gilles; Drider, Djamel
Abstract: Eleven strains of clostridia were isolated from chickens suffering from necrotic enteritis (NE) disease, and were identified by 16S rDNA sequencing as C. perfringens (Clin1, ICVB079, ICVB080, ICVB081, ICVB082, ICVB083, ICVB085, ICVB088, ICVB089, ICVB090), C. sporogenes (ICVB086) and C. cadaveris (ICVB087). These novel strains were then characterized for their pathoproperties including their sensitivity to different antibiotics, hemolytic activities and abilities to carry netB gene, which encodes the necrotic enteritis B-Like toxin (NetB); a key virulence factor involved in the NE. Whilst, no antibiotic resistance was detected for all these strains, C. perfringens ICVB081 and C. perfringens Clin1 have β-hemolytic activities and carry DNA coding for the netB gene. Remarkably, cross-resistant assays performed between these Clostridium strains underpinned the capability of C. perfringens ICVB082 to inhibit the pathogenic C. perfringens DSM756, used as reference strain. This inhibition was exerted through production of an extracellular compound, which was sensitive to heat treatment, lipase and active at pH values ranging from 4 to 7. This report deals with the isolation of novel Clostridium strains from chicken origin and underlines the safety and inhibitory capability of C. perfringens ICVB082 through an extracellular metabolite. Highlights: Interaction Clostridium species. Cross-resistance. Production of extracellular antimicrobial substance: insights and prospects.